Aquaculture Plants and Invertebrates - Diarte-Plata, Genaro; Escamilla-Montes, Ruth (IntechOpen, 2019)
This book is divided into three sections. Following the "Introduction", the second section, "Sustainable Aquaculture", offers integrated information on rice cultivation and aquaculture that provide additional benefits to producers. In addition, the participation of aquaculture in the restoration of the Crassostrea virginica fishery is evaluated. The third section, "Homeopathy and Probiotics", is about highly diluted substances and beneficial microorganisms that have proved their effectiveness in human medicine, agronomy, veterinary and currently in the marine aquaculture field. Also, a study focused on the performance of growth and nutrient utilization of the freshwater shrimp Macrobrachium vollenhovenii fed diets supplemented with Lactobacillus acidophilus is presented. This book can be consulted by students, professors and researchers in the area of biological sciences.